2017
DOI: 10.1088/1361-6560/aa5d46
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of superparamagnetic particles under the influence of high field gradient arrays

Abstract: The aim of this study was to characterize the behaviour of superparamagnetic particles in magnetic drug targeting (MDT) schemes. A 3-dimensional mathematical model was developed, based on the analytical derivation of the trajectory of a magnetized particle suspended inside a fluid channel carrying laminar flow and in the vicinity of an external source of magnetic force. Semi-analytical expressions to quantify the proportion of captured particles, and their relative accumulation (concentration) as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…Our previous work has indicated that the accumulation of magnetic particles in vitro and in vivo strongly depends on the force profile of the magnet and this is further supported by the results of the present study. For the MAD design described here, the total magnetic force from the magnet was optimized at the target depth, but no subsequent attempt was made to tailor the force profile.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our previous work has indicated that the accumulation of magnetic particles in vitro and in vivo strongly depends on the force profile of the magnet and this is further supported by the results of the present study. For the MAD design described here, the total magnetic force from the magnet was optimized at the target depth, but no subsequent attempt was made to tailor the force profile.…”
Section: Discussionsupporting
confidence: 91%
“…This type of force profile typically results in more particles accumulating closer to the edge of the magnet, rather than above the center, resulting in an inefficient accumulation distribution if the target is aligned coaxially with the MAD. Our previous simulation results suggest that force profiles that rapidly vary and peak in a confined spatial region lead to more efficient accumulation of carriers to a coaxially aligned target . The MAD emits this type of force profile beyond z = 15 mm, but at this range, the full‐width half‐maximum (FWHM) of the profile is ≈40 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two different types of magnet array were compared with the magnet array used in this study via numerical modelling. A magnet array made up of pyramidal magnets, and a custom shaped Halbach magnet array based on [Barnsley 2016, Barnsley 2017 were taken into consideration (Fig. 9).…”
Section: F Magnet Array Optimizationmentioning
confidence: 99%